PENGARUH PENAMBAHAN TEPUNG PISANG KEPOK PUTIH TERHADAP SIFAT FISIK DAN SENSORI STIK - muthia damayanti; Wikanastri Hersoelistyorini (Universitas Muhammadiyah Semarang, 2020)
Stick is type of pastry with a frying treatment with oil, usually made from wheat flour and tapioca. Banana flour is one of the flour products that can be used making sticks because they are easily mixed into various preparations and enriched with nutrients. The general objective of this study was to determine the effect of adding white kepok banana flour to physical properties (hardness) and sensory sticks. The research method of banana sticks consisted of 4 treatments of adding white kepok banana flour which were 0, 10, 20 and 30 grams. Each treatment was repeated 6 times, resulting in 24 experimental units. The results showed that there was a significant effect of adding white kepok banana flour to physical characteristics (hardness) and sensory sticks. The best physical and sensory properties were found in the manufacture of sticks with the addition of 10 grams of white kepok banana flour with the results of proximate analysis of water content of 9.74%, ash content of 0.93%, fat content of 35.86%, protein 3.83% and carbohydrates 49 , 64%. The more white kepok banana flour is added, the resulting stick will be harder and produce a more brownish color, caramel aroma and a slightly sweet taste.